Marlojong Custom Contribution In Marriage Dispensation Case At Panyabungan Religious Court - Muhamad Hasan Sebyar; Pagar Pagar; Sukiati Sukiati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Judges at Panyabungan Religious Court explored the prevailing values in society by consulting traditional figures, also known as hatobangon. This is a common practice when a marriage is based on marlojong custom. This study aimed to examine the contribution of customary laws in marriage dispensation decision at Panyabungan Religious Court by using the legal approach and the socio-legal approach. The legal approach was used to analyze marriage dispensation verdict at Panyabungan Religious Court. The socio-legal approach was used to analyze the social interactions that occur between the Religious Courts and customary institutions. The results of this study indicated that traditional leaders play an important role in providing legal advice in society. In cases of underage marriages, usually hatobangon (traditional leaders) propose two options; unregistered marriage or marriage dispensation application. In the latter case, hatobangon play their role assisting in the marriage dispensation request. Well-educated or knowledgeable hatobangon typically recommend submitting a request for marriage dispensation to Panyabungan Religious Court. This hatobangon statement letter serves as one of the requirements for the judge’s approval of marriage dispensation request. The contribution of customary laws reflects a manifestation of the prevailing Islamic values in society. Customary laws provide an alternative way to resolve marriage dispensation cases in the society and are used as an evaluation tool in stipulating a court decision. In addition, customary laws aid the public in understanding the inclusion of the Islamic laws in the state laws, such as age limit for marriage.